The critical influence of carbon on the thermal stability of nanocrystalline Ni–W alloys. (February 2015) - Marvel, Christopher J.; Cantwell, Patrick R.; Harmer, Martin P.
Abstract : The carbide Ni6 W6 C has been identified in electroplated and sputtered nanocrystalline Ni–23 at.% W annealed at 700 °C. This carbide is unexpected and forms due to carbon contamination, which is difficult to avoid in practice. Carbon has a low solubility in the Ni(W) solid solution and may segregate strongly to grain boundaries while W anti-segregation may occur during carbide precipitation. Carbon contamination may therefore impact the thermal stability of nanocrystalline Ni–W in ways not previously considered.